Risk assessment of Escherichia coli O157:h7, Listeria monocytogenes, Salmonella enterica subsp. Enterica serovar typhimurium and Staphylococcus aureus within a stone fruit production environment - Korsten, Lise (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2013.